\(\frac{x^7-x^4}{x^6-1}\)
Giúp vs mn!!
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(-2x^2+x+28\)
\(=-2x^2+8x-7x+28\)
\(=-2x\left(x-4\right)-7\left(x-4\right)\)
\(=\left(x-4\right)\left(-2x-7\right)\)
\(\frac{x-a}{x-b}=\frac{x-b}{x-a}\)
\(\Rightarrow\left(x-a\right)\left(x-a\right)=\left(x-b\right)\left(x-b\right)\)
\(\Leftrightarrow\left(x-a\right)^2=\left(x-b\right)^2\)
\(\Leftrightarrow x^2-2ax+a^2=x^2-2bx+b^2\)
\(\Leftrightarrow a^2-b^2=-2bx+2ax\)
\(\Leftrightarrow\left(a-b\right)\left(a+b\right)=2x\left(a-b\right)\)
\(\Leftrightarrow a+b=2x\)
\(\Leftrightarrow x=\frac{a+b}{2}\)
Hay x là trung bình cộng của a và b
\(\frac{x^7-x^4}{x^6-1}=\frac{x^4.\left(x^3-1\right)}{\left(x^3\right)^2-1}=\frac{x^4.\left(x^3-1\right)}{\left(x^3-1\right)\left(x^3+1\right)}\frac{x^4}{x^3+1}\)
\(\frac{x^7-x^4}{x^6-1}=\frac{x^4\left(x^3-1\right)}{\left(x^3\right)^2-1}=\frac{x^4\left(x^3-1\right)}{\left(x^3-1\right)\left(x^3+1\right)}=\frac{x^4}{x^3+1}\)